A Nietzschean Reading of Androgyny in Virginia Woolf's To the Lighthouse1 - Ayyildiz, Nilay Erdem (Karadeniz Technical University, 2019)
Both Friedrich Nietzsche and Virginia Woolf are of the opinion that a human being is comprised of two opposite selves. They are, in Nietzsche's terms, the Apollonian deriving from Apollo, the sun-god associated with self-control, rationality and order, and the Dionysian named after Dionysus, the wine-god, representing passion, irrationality, and chaos. In Woolf's understanding, the human mind is composed of masculine and feminine characteristics. From their perspectives, the patriarchal Victorian culture brought the Apollonian self forward the Dionysian one and associated 'woman' with the Dionysian and feminine traits such as emotion, passion and chaos but 'man' with the Apollonian and masculine properties including reason, self-control and order. Nietzsche notes in The Birth of Tragedy (1872) that an artist creates a high-quality art out of the balance between his Apollonian and Dionysian selves, and Woolf claims in A Room of One's Own (1929) that the fusion of an artist's masculine and feminine minds is prerequisite for creativity. Therefore, both of them necessitate for a great artist to produce free from gender traits and call for the androgynous mind. Thus, this paper explores the intersection of Nietzsche's Apollonian-Dionysian dichotomy and Woolf's theory of androgyny in To the Lighthouse (1927). © 2019 Karadeniz Technical University. All rights reserved.
Keywords: A Room of One's Own; Nietzsche; The Birth of Tragedy; To the Lighthouse; Woolf